Reliability analysis of a pile foundation in a residual soil: contribution of the uncertainties involved and partial factors - Teixeira, Ana (2011)
Reliability evolved from other areas, such as structures, requiring special adaptation when applied to geotechnical engineering. This paper shows one way to treat geotechnical uncertainties in a simple way. A sensitivity analysis, based on a series of calculations of the probability of failure for a single pile foundation is done in order to investigate the influence of each uncertainty source in reliability index. This experimental pile was installed in a residual soil in Portugal and was designed to withstand a vertical axial load. It was found, for this experimental case study, that the most important uncertainty source comes from model error, and not from the soil’s spatial variability and uncertainty. Finally, the procedure to evaluate the resistance and load partial safety factors is shown and, for the same pile foundation, the safety factors are calculated and compared to the ones recommended by the Eurocode 7. Both methodologies are based on Monte Carlo simulation technique.